Language Planning in Nigeria: Clash Between English Language and Indigenous Languages - Eneremadu, Queen Easther Chioma; Rosita, Ndubuaku; Eziku, Chuwuezi (PT FORMOSA CENDEKIA GLOBAL, 2024)
In Nigeria almost 500 indigenous language that has assumed the status of a global linguistic code. The contact in different domains between English language an contact languages in the country continues to effect the performance in English and contact languages thereby making communication in either English or any other indigenous languages unattainable. This research work studied the gap between the use of English language and the indigenous languages in multilingual country, Nigeria which exists as a result of the non-implementation of language policies as stipulated by the Government. The sampling research method was adopted and questionnaires were employed to test the research hypothesis which proved positive. The major conclusion deduced from the findings reflect that if there must exist a linguistic balance between the use of English language in the country, the Government must endeavour through the Ministries of Education that both public owned and private owned schools adhere to a new language policy as the research work suggests. Offering indigenous languages in schools must be made compulsory and not optional as well as a compulsory subject to gain admission into Nigerian Universities like the English language.